National Effort to Re-Establish Heavy Ion Cancer Therapy in the United States - Pompos, Arnold; Foote, Robert L.; Koong, Albert C.; Le, Quynh Thu; Mohan, Radhe; Paganetti, Harald; Choy, Hak (Frontiers in Oncology, 2022)
In this review, we attempt to make a case for the establishment of a limited number of heavy ion cancer research and treatment facilities in the United States. Based on the basic physics and biology research, conducted largely in Japan and Germany, and early phase clinical trials involving a relatively small number of patients, we believe that heavy ions have a considerably greater potential to enhance the therapeutic ratio for many cancer types compared to conventional X-ray and proton radiotherapy. Moreover, with ongoing technological developments and with research in physical, biological, immunological, and clinical aspects, it is quite plausible that cost effectiveness of radiotherapy with heavier ions can be substantially improved.